Mesoporous bioceramic filter sponge, its preparation method and application

CN121796990BActive Publication Date: 2026-10-09HUBEI SHENGLAN ENVIRONMENTAL CONSTR CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610029893.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-01-11
Publication Date
2026-10-09
Estimated Expiration
2046-01-11

AI Technical Summary

Technical Problem

[0006]本发明旨在提供一种物理除菌灭毒的介孔生物陶瓷海绵滤材,解决现有滤材杀菌能力不足或依赖化学药剂的问题,实现高效、安全的微生物物理灭活,并能够选择性去除有害污染物而保留有益成分

Benefits of technology

(1)高效安全的物理灭活能力:通过独特的“吸附-锁定-刺破”物理机制灭活微生物,不添加任何化学杀菌剂,从源头上杜绝了化学残留、有害副产物和微生物耐药性问题;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121796990B_ABST
    Figure CN121796990B_ABST
Patent Text Reader

Abstract

The application discloses a mesoporous bioceramic filter sponge as well as a preparation method and application thereof, and belongs to the technical field of water treatment and air purification. The filter sponge adopts a three-layer composite structure, and comprises a three-dimensional porous sponge framework, a mesoporous ceramic transition layer and a nano metal thorn functional layer. Microorganism inactivation is realized through a unique 'adsorption-locking-piercing' physical mechanism, the inactivation rate of bacteria and viruses is more than 99.9% under the condition of not using chemical agents, and heavy metal pollutants can be selectively removed while beneficial minerals are retained. The filter sponge has the advantages of high porosity, large specific surface area, long service life and the like, and can be widely applied to the fields of drinking water treatment, sewage treatment and air purification.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of water treatment and air purification technology, specifically relating to a mesoporous bioceramic filter sponge, its preparation method, and its application. Background Technology

[0002] Traditional physical filtration technologies, such as HEPA filters, are effective at intercepting PM2.5 and bacteria, but they have limited ability to intercept even smaller virus particles and cannot inactivate trapped microorganisms, allowing them to multiply on the filter and cause secondary pollution. While reverse osmosis (RO) technology can efficiently remove various pollutants, including heavy metals and viruses, its indiscriminate filtration method also removes beneficial minerals such as calcium and magnesium, potentially posing health risks with long-term consumption of such water. Furthermore, the high flow resistance of RO membranes leads to high energy consumption and low water production rates.

[0003] Chemical sterilization technologies, such as chlorine disinfection, ozone, and ultraviolet light, carry the risk of chemical residues or the generation of harmful byproducts. For example, ozone itself is a pollutant, and its sterilization effect lacks sustainability. Furthermore, equipment maintenance costs and energy consumption are relatively high.

[0004] Activated carbon, a representative of adsorption technology, has a limited adsorption capacity and is easily saturated. Once saturated, it not only becomes ineffective but may also become a source of pollutant release. Furthermore, it lacks sterilization capabilities, and the adsorbed microorganisms may proliferate, causing secondary pollution. Some composite filter materials on the market attempt to integrate multiple technologies, but they still struggle to overcome key industry pain points such as the risk of silver ion leaching, the requirement for specific wavelengths of ultraviolet light to function in photocatalytic materials, and most importantly, the inability to achieve "selective filtration"—that is, precisely removing harmful substances while retaining beneficial components.

[0005] These limitations collectively point to an urgent need for a new generation of purification technology: it needs to have the ability to efficiently physically inactivate microorganisms and avoid chemical residues; it needs to be able to intelligently distinguish and selectively remove harmful substances; and it needs to be long-lasting, low-energy, and low-maintenance. Summary of the Invention

[0006] The present invention aims to provide a mesoporous bioceramic sponge filter material for physical sterilization and disinfection, which solves the problems of insufficient sterilization ability or reliance on chemical agents in existing filter materials, achieves efficient and safe physical inactivation of microorganisms, and can selectively remove harmful pollutants while retaining beneficial components.

[0007] The technical solution of this invention is implemented as follows: In a first aspect, the present invention provides a mesoporous bioceramic filter sponge, characterized in that it comprises the following three-layer composite structure: a three-dimensional porous sponge skeleton, a mesoporous ceramic transition layer, and a nano-metal spike functional layer; wherein the mesoporous ceramic transition layer is loaded on the surface of the three-dimensional porous sponge skeleton; the nano-metal spike functional layer is located on the inner wall of the pores of the mesoporous ceramic transition layer and contains nano-sized zero-valent iron and zero-valent silver crystals.

[0008] Based on the above technical solutions, preferably, the Ag / Fe mass ratio in the nano-metal spike functional layer is 0.18:1-0.38:1. Zero-valent iron serves as the main component for physical cell disruption and heavy metal reduction; the Ag / Fe mass ratio stabilizes zero-valent iron, inhibits its oxidation, and produces a synergistic antibacterial effect.

[0009] By in-situ growing nanoscale zero-valent iron and zero-valent silver crystals with sharp structures on the inner wall of mesoporous channels, an array of "nanometallic spikes" is constructed to achieve physical cell wall disruption and inactivation of microorganisms and selective reduction and removal of heavy metals. Utilizing the sharp geometric structure of the nanometallic spikes, with a radius of curvature <5nm, they generate extremely high local stress on viral capsids or bacterial cell walls under fluid shear force, directly mechanically cutting and destroying their structural integrity, leading to leakage of genetic material or inactivation of key functional proteins, thus achieving broad-spectrum, drug-free physical disinfection. The strong reducing properties of nano-zero-valent iron can specifically target highly toxic heavy metal ions, such as Cr... 6+ Reduced to Cr 3+ Pb 2+ Restored to Pb 0 This causes it to precipitate and fix; while for Ca 2+ Mg 2+ K + Beneficial mineral ions hardly react, thus achieving intelligent purification that "removes harm and preserves benefit".

[0010] More preferably, the porosity of the three-dimensional porous sponge skeleton is 86%, and the specific surface area is 300-500 m². 2 / g. The three-dimensional porous sponge skeleton has a micron-scale open-pore structure, with the pore size distribution of its loaded mesoporous ceramic transition layer and the overall composite material ranging from 2-50 nm. Its three-dimensional interconnected network structure mainly undertakes medium- to high-efficiency filtration tasks, deeply intercepting colloids, large molecular organic matter, and some microorganisms, and has a strong adsorption capacity for volatile organic compounds. Simultaneously, its huge specific surface area and optimized surface chemical properties give it an extremely strong adsorption capacity for volatile organic compounds (VOCs), formaldehyde, residual chlorine, and odor molecules, making it a key component of deep purification.

[0011] Further preferably, the matrix material of the three-dimensional porous sponge skeleton includes polyether polyol, diatomaceous earth, kaolin, and mullite, wherein the mass percentage of each component is: diatomaceous earth 30-50%, kaolin 20-35%, mullite 5-15%, and the balance is polyether polyol, with the total mass percentage of each component being 100%. Polyether polyol, as the main pore-forming agent, provides flexibility and forms a macroporous framework; diatomaceous earth provides natural macropores (>50 nm) and main adsorption sites, possessing a huge specific surface area, and is the main source of the skeleton's adsorption capacity. The trace metal impurities it contains (such as Fe and Al) and the added refined carbon powder can form a catalytic system at high temperatures, synergistically promoting the catalytic oxidation of acidic gaseous pollutants such as formaldehyde and converting them into salts for fixation. In some scenarios, water-soluble starch is added as an auxiliary pore-forming agent and reinforcing agent; its molecular chains can intertwine to form a finer network structure and improve the strength of the skeleton; kaolin and mullite are used to ensure the overall thermal stability, chemical inertness, and sufficient mechanical strength of the skeleton.

[0012] Further preferably, the pore size of the mesoporous ceramic transition layer is concentrated in the range of 2-50 nm. Pores that are too large (>50 nm) will lead to virus screening failure and a sharp reduction in specific surface area; pores that are too small (<2 nm) will cause a dramatic increase in transport resistance, accidental interception of beneficial minerals, and easy pore blockage. This pore size design is a physical interception window optimized for virus size, effectively trapping bacterial and viral aggregates while maintaining low flow resistance and preventing accidental interception of beneficial minerals. This layer is highly ordered and uniformly attached to the surface of the three-dimensional sponge skeleton in the form of nanoscale particles, including the outer surface and the inner walls of all internal pores, greatly increasing the usable specific surface area. Its nanoscale rough structure provides a large number of strong anchoring points for subsequent loading of zero-valent iron and zero-valent silver metal spikes, which is the basis for achieving high load capacity and high stability.

[0013] More preferably, the mesoporous ceramic transition layer comprises the following components by mass percentage: 50%-60% sodium-based bentonite, 5% refined carbon powder, 15% water-soluble starch, with the balance being a binder phase, and the total mass percentage of all components being 100%. The mesoporous material prepared from sodium-based bentonite has regular channels and abundant exchangeable sodium ions. This enables it to efficiently adsorb and remove heavy metal cations (such as Pb) from water through ion exchange. 2+ Cd 2+ Cu 2+ (etc.) and ammonium ions (NH4+) + Simultaneously, its surface active sites can physically adsorb polar organic matter, residual chlorine, pigments, and odor molecules, undertaking the initial purification task. Furthermore, through ion exchange balance, it helps retain beneficial minerals such as calcium and magnesium in the water. The binder phase is an inorganic sol.

[0014] More preferably, the matrix material of the nano-metal spike functional layer further includes 40%-50% inorganic sol as a high-temperature binder to ensure that the nano-metal spikes are firmly loaded on the macroporous-mesoporous ceramic framework.

[0015] In a second aspect, the present invention provides a method for preparing the mesoporous bioceramic filter sponge described in the first aspect, comprising the following steps: S1. Mix polyether polyol, diatomaceous earth, kaolin and mullite in proportion to prepare a three-dimensional porous polyether polyol sponge skeleton. S2. Grind sodium bentonite, refined carbon powder, water-soluble starch, binder phase, silver salt and iron salt to prepare impregnation slurry; S3. Immerse the skeleton obtained in step S1 into the slurry in step S2, and then vacuum and pressurize it. S4. Sintering at a programmed temperature to form a mesoporous structure on the surface of the substrate at 450-500℃; S5. A nano-metal spike functional layer is generated by reduction in a nitrogen-hydrogen mixed atmosphere to obtain the mesoporous bioceramic filter sponge.

[0016] Based on the above technical solutions, preferably, the viscosity of the impregnation slurry in step S3 is 500-1000 cP, the vacuum pressure is -0.08 MPa, and the pressurization pressure is 0.3-0.5 MPa.

[0017] A further preferred embodiment of the process for the programmed temperature rise sintering in step S4 is as follows: first, raise the temperature to 300-350℃ and hold for 1 hour, then raise the temperature to 450-500℃ and hold for 2-4 hours.

[0018] More preferably, the volume concentration of H2 in the nitrogen-hydrogen mixture in step S5 is 5%-10% to control the thoroughness and mildness of the reduction reaction and avoid excessive reduction that could lead to particle agglomeration.

[0019] Thirdly, the present invention provides the application of the mesoporous bioceramic filter sponge described in the second aspect in air purification and water treatment.

[0020] The filter material of this invention has the following significant advantages compared with the prior art: (1) Highly efficient and safe physical inactivation capability: Microorganisms are inactivated through a unique "adsorption-lock-puncture" physical mechanism without the addition of any chemical bactericides, thus eliminating chemical residues, harmful byproducts and microbial resistance problems from the source; (2) Excellent structural stability and long lifespan: The ceramic matrix and functional layer are bonded by chemical bonds, preventing the coating from peeling off during use. Nano-zero valent iron is confined within the mesoporous channels, preventing its agglomeration and oxidation, and maintaining long-term activity. Laboratory accelerated life tests show that under continuous operation conditions, the microbial inactivation efficiency of this filter material does not decrease significantly within 9 months (>6 months), and its lifespan far exceeds that of traditional activated carbon filter cartridges (usually 1-3 months). (3) Flexible application and low operating cost: The three-dimensional sponge structure provides extremely low flow resistance, making it suitable for various scenarios from household water purifiers to large-scale water plants. It is washable and regenerable; surface contaminants can be removed by reverse water flow or dilute acid cleaning, restoring most of its performance and significantly reducing long-term operating costs. (4) Environmentally friendly: The main components of the material are natural elements such as silicon, sodium, and iron. There is no risk of heavy metal leaching to the environment after disposal, and it can be safely disposed of. Attached Figure Description

[0021] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0022] Figure 1 This is a schematic diagram of the overall structure of the mesoporous bioceramic sponge filter material of the present invention, wherein 101 is a three-dimensional porous ceramic sponge skeleton; 102 is a mesoporous ceramic transition layer (loaded on the surface of the skeleton); and 103 is a nano-metal spike functional layer (located in the mesoporous channels). Figure 2 This is a schematic diagram of the microstructure of the nano-metal spike functional layer of the present invention (partially enlarged), wherein 103-1 is nano-zero-valent iron particles (exhibiting a sharp polyhedral structure); 102-1 is a mesoporous ceramic channel; Figure 3 This is a schematic diagram of the physical inactivation process of the virus according to the present invention, wherein 201 is a virus particle; S1 is the adsorption and locking stage; S2 is the physical cell disruption stage (the virus comes into contact with the nano-metal spikes); and S3 is the inactivation and deactivation stage (the virus structure is destroyed). Detailed Implementation

[0023] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0024] Table 1: Material Source Description Table

[0025] Example 1 S1. Mix 22g of polyether polyol, 40g of diatomaceous earth, 28g of kaolin and 10g of mullite, and prepare a three-dimensional porous sponge skeleton by conventional polyurethane foaming process. S2. Immerse the sponge matrix in 125g of water mixed with 55g sodium bentonite, 15g water-soluble starch, 5g refined carbon powder, and 25g PVA sol. Then add 20g Fe2O3 and 5g Ag2O to the slurry (Ag / Fe mass ratio is 0.25:1). The mixed particles are ball-milled in a mixing device at a ball-to-particle ratio of 10:1, a rotation speed of 300rpm, and a ball milling time of 1 hour to ensure that the powder is uniformly mixed at the submicron scale with a particle size ≤12μm. The solid content of the slurry is controlled at 50%, and the viscosity is measured at 25℃ to be 800cP. S3. Immerse the skeleton obtained in step S1 into the slurry of step S2, remove the air in the matrix pores under a vacuum of -0.08 MPa, and then apply a positive pressure of 0.4 MPa for 5 minutes to allow the slurry to fully penetrate. S4. The mixture is sintered to 320°C and held for 1 hour through a program, and then raised to the final high-temperature sintering temperature of 480°C and held for 2 hours to form a mesoporous structure. S5. In a nitrogen-hydrogen mixture with a volume concentration of 8% H2, the precursor is reduced at 480°C to convert it into zero-valent iron and zero-valent silver nanoparticles, thus obtaining the mesoporous bioceramic filter sponge.

[0026] Example 2 S1. Mix 40g of polyether polyol, 30g of diatomaceous earth, 25g of kaolin and 5g of mullite, and prepare a three-dimensional porous sponge skeleton by conventional polyurethane foaming process. S2. Immerse the sponge matrix in 130g of water mixed with 50g sodium bentonite, 15g water-soluble starch, 5g refined carbon powder, and 30g PVA sol. Then add 25.42g Fe2O3 and 4.58g Ag2O (Ag / Fe mass ratio of 0.18:1). The mixed particles are ball-milled in a mixing device at a ball-to-particle ratio of 10:1, a speed of 300rpm, and a ball milling time of 1 hour to ensure that the powder is uniformly mixed at the submicron scale with a particle size ≤12μm. The solid content of the slurry is controlled at 50%, and the viscosity is measured at 25℃ to be 500cP. S3. Immerse the skeleton obtained in step S1 into the slurry of step S2, remove the air in the matrix pores under a vacuum of -0.08 MPa, and then apply a positive pressure of 0.3 MPa for 5 minutes to allow the slurry to fully penetrate. S4. The mixture is sintered to 300°C and held for 1 hour through a program, and then raised to the final high-temperature sintering temperature of 450°C and held for 2 hours to form a mesoporous structure. S5. In a nitrogen-hydrogen mixture with a volume concentration of 5% H2, the precursor is reduced at 480°C to convert it into zero-valent iron and zero-valent silver nanoparticles, thus obtaining the mesoporous bioceramic filter sponge.

[0027] Example 3 S1. Mix 50g of diatomaceous earth, 35g of kaolin and 15g of mullite, and prepare a three-dimensional porous sponge skeleton by conventional polyurethane foaming process. S2. Immerse the sponge matrix in 120g of water mixed with 60g sodium bentonite, 15g water-soluble starch, 5g refined carbon powder, and 20g PVA sol. Then add 14.49g Fe2O3 and 5.51g Ag2O (Ag / Fe mass ratio of 0.38:1). The mixed particles are ball-milled in a mixing device at a ball-to-particle ratio of 10:1, a rotation speed of 300rpm, and a ball milling time of 1 hour to ensure that the powder is uniformly mixed at the submicron scale with a particle size ≤12μm. The solid content of the slurry is controlled at 50%, and the viscosity is measured at 25℃ to be 1000cP. S3. Immerse the matrix obtained in step S1 into the slurry obtained in step S2, remove the air from the pores of the matrix under a vacuum of -0.08 MPa, and then apply a positive pressure of 0.5 MPa for 5 minutes to allow the slurry to fully penetrate. S4. The mixture is heated to 350°C and held for 1 hour, then heated to 500°C and held for 2 hours to form a mesoporous structure. S5. In a nitrogen-hydrogen mixture with a volume concentration of 10% H2, the precursor is reduced at 480°C to convert it into zero-valent iron and zero-valent silver nanoparticles, thus obtaining the mesoporous bioceramic filter sponge.

[0028] Examples 4-7 Unlike Example 1, in Example 4, Fe2O3 was 21.19g, Ag2O was 5.51g, and the Ag / Fe mass ratio was 0.18:1; in Example 5, Fe2O3 was 18.12g, Ag2O was 6.88g, and the Ag / Fe mass ratio was 0.38:1; in Example 6, Fe2O3 was 22.73g, Ag2O was 2.27g, and the Ag / Fe mass ratio was 0.10:1; in Example 7, Fe2O3 was 16.67g, Ag2O was 8.33g, and the Ag / Fe mass ratio was 0.50:1. The remaining parameters and steps were the same as in Example 1, and will not be repeated here.

[0029] Comparing Example 1 with Examples 6 and 7, it is evident that zero-valent iron in Example 1 exhibits the best stability and the strongest synergistic effect with silver, achieving a virus inactivation rate >99.99%. In Example 6, zero-valent iron is easily oxidized and deactivated, resulting in poor stability and a virus inactivation rate of approximately 90%. In Example 7, due to excessive silver, some iron active sites are partially covered, leading to high costs; the virus inactivation rate is approximately 97%, still lower than that of Example 1. Therefore, the Ag / Fe mass ratio directly affects the stability and synergistic bactericidal effect of nanoparticles.

[0030] Examples 8-11 Unlike Example 1, the final high-temperature sintering temperatures were 450°C, 500°C, 300°C and 600°C, respectively. The remaining parameters and steps were the same as in Example 1, and will not be repeated here.

[0031] Comparing Example 1 with Examples 10 and 11, it can be seen that the nanoparticles in Example 1 have uniform morphology, an initial inactivation rate of >99.99% against E. coli, and an inactivation rate of >98% after 60 days of accelerated aging. Example 10, due to its low final sintering temperature, resulted in insufficient reduction, poor crystallinity, and indistinct spike structure, with an initial inactivation rate of approximately 95% against E. coli, which rapidly decreased to <80% after 60 days of accelerated aging. Example 11, due to its high final sintering temperature, showed significant particle growth exceeding 30 nm, blunted spikes, and a small specific surface area, with an initial inactivation rate of approximately 97% against E. coli, and a stable but initially low inactivation rate after 60 days of accelerated aging. Therefore, sintering temperature directly affects atomic mobility and crystal growth kinetics, and is a core factor controlling the size, crystallinity, and spike morphology of nanoparticles.

[0032] Comparative Example 1 Unlike Example 1, Comparative Example 1 does not have a nano-metal spike functional layer. The remaining parameters and steps are the same as in Example 1, and will not be repeated here.

[0033] A comparison of Example 1 and Comparative Example 1 shows that without the nano-metal spike functional layer, the bacterial and viral removal rates are significantly reduced (bacterial inactivation rate drops from 99.99% to 70%-89% <mainly relying on physical interception and antibacterial properties of the mesoporous material surface>; virus removal rate drops from 99.99% to 60%-85% <mainly relying on physical sieving of the mesoporous structure>); the purification speed decreases with increasing pollutant load; and the long-term purification function decays rapidly. Therefore, the nano-metal spike functional layer is the core factor determining whether this filter material can achieve efficient, rapid, and long-lasting sterilization and disinfection. Its physical puncture mechanism not only significantly improves immediate purification efficiency but also ensures high efficiency and stability throughout the product's entire lifecycle by avoiding the development of microbial resistance. This "one-piece molding, step-by-step functionalization" process design successfully integrates physical interception, chemical adsorption, and mechanical killing functions, achieving a synergistic purification goal.

[0034] As shown in Table 2-4, according to authoritative third-party tests conducted by the Guangzhou Institute of Microbiology and other institutions (using bacterial and viral sampling and detection equipment), the inactivation efficiency of various common pathogenic microorganisms in the air exceeded 99%. Specific data can be found in the attached data table.

[0035] Testing basis and methods: a) GB / T 18801-2022 Air purifiers and GB 21551.3-2010 Special requirements for air purifiers with antibacterial, sterilization and purification functions for household and similar electrical appliances.

[0036] b) GB / T 21551.2-2024 Antibacterial, sterilization and purification functions of household and similar electrical appliances - Part 2: Particular requirements for antibacterial materials - Appendix A Test methods for antibacterial properties of materials - A.5.3 Vibration method.

[0037] c) GB / T 21551.2-2024 Antibacterial, sterilization and purification functions of household and similar electrical appliances - Part 2: Particular requirements for antibacterial materials.

[0038] Table 2: Antibacterial rate parameters against Staphylococcus aureus

[0039] Table 3: Influenza virus H1N1 removal rate parameters

[0040] Table 4: Performance Comparison with Traditional Filter Media The comparison indicators include: bacterial inactivation rate, virus inactivation rate, heavy metal removal rate, beneficial mineral retention rate, and service life.

[0041]

[0042] Data Explanation: 1. The virus inactivation test was completed by a biosafety laboratory with CNAS accreditation; 2. Heavy metal and mineral testing uses the standard spiking method, with concentrations simulating actual polluted water quality; 3. Service life is estimated based on household water purification conditions (200L of water processed per day); This filter media can be used alone or in conjunction with an RO membrane as a pretreatment unit to protect the RO membrane and extend its lifespan by 2-3 times.

[0043] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A mesoporous bioceramic filter sponge, characterized in that, It includes the following three-layer composite structure: a three-dimensional porous sponge skeleton, a mesoporous ceramic transition layer, and a nano-metal spike functional layer; The mesoporous ceramic transition layer is loaded on the surface of the three-dimensional porous sponge skeleton; the nano-metal spike functional layer is located on the inner wall of the pores of the mesoporous ceramic transition layer and contains nano-sized zero-valent iron and zero-valent silver crystals. The porosity of the three-dimensional porous sponge skeleton is 86%, and the specific surface area is 300-500 m². 2 / g; The pore size of the mesoporous ceramic transition layer is concentrated in the range of 2-50 nm; In the nano-metal spike functional layer, the Ag / Fe mass ratio is 0.18:1-0.38:1; The matrix material of the three-dimensional porous sponge skeleton includes polyether polyol, diatomaceous earth, kaolin, and mullite, wherein the mass percentage of each component is: diatomaceous earth 30-50%, kaolin 20-35%, mullite 5-15%, and the balance is polyether polyol, and the total mass percentage of each component is 100%. The mesoporous ceramic transition layer comprises the following components by mass percentage: 50%-60% sodium-based bentonite, 5% refined carbon powder, 15% water-soluble starch, with the balance being a binder phase, and the total mass percentage of each component is 100%.

2. A method for preparing the mesoporous bioceramic filter sponge as described in claim 1, characterized in that, Includes the following steps: S1. Mix polyether polyol, diatomaceous earth, kaolin and mullite in proportion to prepare a three-dimensional porous polyether polyol sponge skeleton. S2. Grind sodium bentonite, refined carbon powder, water-soluble starch, binder phase, silver salt and iron salt to prepare impregnation slurry; S3. Immerse the skeleton obtained in step S1 into the slurry in step S2, and then vacuum and pressurize it. S4. Programmed temperature rise sintering, at 450-500℃, forms a mesoporous structure on the surface of the matrix material of the three-dimensional porous sponge skeleton; S5. A nano-metal spike functional layer is generated by reduction in a nitrogen-hydrogen mixed atmosphere to obtain the mesoporous bioceramic filter sponge.

3. The preparation method according to claim 2, characterized in that, The viscosity of the impregnation slurry in step S3 is 500-1000 cP, the vacuum pressure is -0.08 MPa, and the pressurization pressure is 0.3-0.5 MPa.

4. The preparation method according to claim 2, characterized in that, The specific process of the programmed temperature rise sintering in step S4 is as follows: first, raise the temperature to 300-350℃ and hold for 1 hour, then raise the temperature to 450-500℃ and hold for 2-4 hours.

5. An application of the mesoporous bioceramic filter sponge as described in claim 1 in air purification.

Citation Information

Patent Citations

  • Carbon-containing membrane for water and gas separation

    CN108124433A

  • Mesoporous ceramic / chlorinated polypropylene carbonate sound insulation foam core material and preparation method thereof

    CN119708803A